2022
DOI: 10.3390/ijms232012695
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glycolysis and Fatty Acid Synthesis in the Activation and T Cell-Modulating Potential of Dendritic Cells Stimulated with a TLR5-Ligand Allergen Fusion Protein

Abstract: Trained immune responses, based on metabolic and epigenetic changes in innate immune cells, are de facto innate immune memory and, therefore, are of great interest in vaccine development. In previous studies, the recombinant fusion protein rFlaA:Betv1, combining the adjuvant and toll-like receptor (TLR)5-ligand flagellin (FlaA) and the major birch pollen allergen Bet v 1 into a single molecule, significantly suppressed allergic sensitization in vivo while also changing the metabolism of myeloid dendritic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Our previous publications showed rFlaA:Betv1 to activate different cell types involved in allergic responses, resulting in the suppression of allergen-induced Th2 inflammation ( 3 , 5 7 , 14 , 15 ). In these studies, the rFlaA:Betv-induced IL-1β secretion was shown to be differently regulated by different types of APCs, including mDCs and BMDMs ( 3 , 5 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous publications showed rFlaA:Betv1 to activate different cell types involved in allergic responses, resulting in the suppression of allergen-induced Th2 inflammation ( 3 , 5 7 , 14 , 15 ). In these studies, the rFlaA:Betv-induced IL-1β secretion was shown to be differently regulated by different types of APCs, including mDCs and BMDMs ( 3 , 5 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, rFlaA:Betv1 efficiently suppressed sensitization towards Bet v 1 in vivo ( 3 ) while also activating mouse bone marrow-derived myeloid dendritic cells (mDCs) ( 3 , 7 , 14 ), bone marrow-derived macrophages (BMDMs) ( 5 ), lung epithelial cells ( 15 ), and naïve mouse and human B cells ( 6 ) more strongly than the equimolar mixture of both proteins either provided alone or as a non-fused mixture. Here, rFlaA:Betv1 induced a pro-inflammatory cytokine production and the subsequent formation of Bet v 1-specific Th1 responses with Th2-suppressing capacity while also mediating a prominent production of the anti-inflammatory cytokine IL-10 in all investigated types of APCs (mDCs ( 3 , 7 , 14 ), BMDMs ( 7 ), and B cells ( 8 )), which was shown to significantly suppress Th2 responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To modulate allergen-specific immune responses, TLR-ligand allergen fusion proteins combining allergens or allergen peptides with an inherent adjuvant activity were proposed and recently reviewed by Blanco-Pérez et al ( Blanco-Pérez et al, 2019 ). Despite promising preclinical data regarding the induction of immunotolerance by the fusion proteins, i.e., for the birch pollen allergen Bet v 1 fused to flagellin, or T cell peptides of the peach LTP Pru p 3 conjugated to TLR7 and TLR4 ligand, so far none of the candidates were clinically evaluated ( Schülke et al, 2010 ; Losada Méndez et al, 2021 ; Goretzki et al, 2022 ).…”
Section: Tlrs In Treatment Of Allergic Diseasesmentioning
confidence: 99%
“…Considering that NOD2 adjuvants are used in vaccine design to boost immune responses, whereas care needs to be taken in asthmatics, those might be used in non-sensitized individuals. Goretzki et al [5], investigated in their highly ambitious study the metabolic mechanisms behind the activation and T cell-modulating potential of DCs stimulated with a fusion protein combining Toll-like (TLR) 5 ligand flagellin (FlaA) and major birch pollen allergen Bet v 1 into a single molecule (rFlaA:Betv1). They found that the effector function of rFlaA:Betv1-activated myeloid DCs mainly depended on glycolysis, with fatty acid synthesis also substantially participating in rFlaA:Betv1-mediated secretion of cytokines, production of antimicrobial molecules, as well as modulation of T cell responses.…”
mentioning
confidence: 99%